PEMBERDAYAAN KELEMBAGAAN BADAN PERMUSYAWARATAN DESA - Jamaluddin, Yanhar (UIR PRESS, 2015)
Badan Permusyawaratan Desa ( BPD) represent institute of delegation of resident of countryside [of] pursuant to regional keterwakilan and specified democratically. BPD function to Study and agree on Device of Regulation of Countryside with Countryside Head ; Accomodating and channelling aspiration socialize countryside, and ; [Doing/Conducting] observation of performance Lead Countryside. Thereby BPD of strategic sharing realize governance of democratic countryside, partisipative, transparent, and akuntabel. Pursuant to analysis and solution descriptively qualitative, showing BPD not yet optimal in executing [his/its] function and role. This Realita [is] caused [by] [his/its] strength predominate Countryside Head, internal factor and also eksternal [in] BPD, and not yet owned vision and missi. For the reason Enableness of aspect of institute of BPD require to be [done/conducted] to increase [his/its] function and role, that is by ; Identifying strength and institute feebleness, Develop;Building komitmen with, Forming community network, Creating excellence, and Map System and Culture of Quality Work. To succeed [it] execution of enableness of institute BPD, needed [by] design program enableness of integrated institute mounted [by] area as according to independence and potency socialize Countryside